Effect of Workload, Work Environment, Work Stress on Employee Performance of Private Universities in the City of Bandung, Indonesia - Jaja Jahari (International Journal of Science and Society, 2019)
The purpose of this study was to determine the effect of workload, work environment, and work stress on the performance of employees of private universities in the city of Bandung, Indonesia. This research uses a descriptive verification method which was conducted on 150 employees of private universities in the city of Bandung. Data collection techniques in this study used questionnaires. Data analysis techniques using correlation analysis, regression, determination and hypothesis testing (t-test). The results of hypothesis testing prove that workload has a negative effect on employee performance, the work environment has a positive effect on employee performance, and work stress has a negative effect on employee performance.